The significance of archaeological source data - Tanner, Pat (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
All archaeology is contingent on the source data and everything stems from that. Achieving a detailed understanding of both the object and the processes is predicated on the quality of the underlying source data. Past reconstruction projects may have used the source data, but it is not always possible to understand or interrogate how that source data has been used or interpreted, due to the lack of published paradata. This paper examines the development of methods employed in the surveying of an archaeological excavation site, in essence the capture and recording of the raw primary data from the site or artefact.